Conocimiento y práctica sobre medidas preventivas del dengue en comerciantes del puerto Masusa Iquitos 2021 - Vela Peña, Tania Peysy (2022)
The objective of the research was to determine the association between the knowledge and practice on preventive measures of Dengue in merchants from 18 to 65 years of age of both sexes of Puerto Masusa Iquitos 2021, the study was Quantitative with a non-experimental, correlational design; the population was made up of 170 and the sample was 118 merchants from 18 to 65 years of both sexes from Puerto Masusa de Iquitos. The technique that was used was the interview, the instruments were the questionnaire of knowledge about Dengue (Validity 91,6% and Reliability 89,7%), and the questionnaire of practices of preventive measures of Dengue (Validity 92,8% and reliability 90,0%). The study evidences the prevalence of low knowledge with 61,0%, followed by the médium leve lof knowledge with 25,4% and the high leve lof knowledge with 13,6%; the practices on preventive measures of Dengue, is predominance incorrect with 81,4%, followed by correct practices with 18,6%, they found (X2 = 38,758; for p = 0,000 < 0,05 and gl = 2). Therefore, it is concluded that there is a statistical association between knowledge and practice on preventive measures of Dengue in merchants from 18 to 65 years of both sexes of Puerto Masusa Iquitos 2021.